2018
DOI: 10.1111/liv.13678
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the progesterone receptor predisposes to HEV infection in HIV‐positive patients

Abstract: Background and AimsInfection with Hepatitis E virus (HEV) can cause chronic liver disease in immunocompromised hosts. In transplant recipients, the use of certain immunosuppressants and food habits has been proposed as risk factors for HEV. In individuals infected with the human immunodeficiency virus (HIV), risk factors for HEV infection are less clear. We aimed to study the association between a mutation in the progesterone receptor (PR) named PROGINS and HEV‐infected in HIV‐positive individuals.MethodsWe ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…In line with the present study, Debes and colleagues demonstrated another link of steroid hormones and immunological cofactors . They found that a mutation in the progesterone receptor was associated with the anti‐HEV seroprevalence in HIV‐positive individuals.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In line with the present study, Debes and colleagues demonstrated another link of steroid hormones and immunological cofactors . They found that a mutation in the progesterone receptor was associated with the anti‐HEV seroprevalence in HIV‐positive individuals.…”
supporting
confidence: 90%
“…Increased IL‐12 levels and a reduced CD4 + and CD8 + T‐cell function were associated with a mutation of the progesterone receptor. These data confirm the link between HEV infection, steroid hormones and an altered immune response …”
supporting
confidence: 82%
“…Two previous studies found the opposite situation, namely that PROGINS mutations could be a risk factor for HEV infection (Bose et al, 2011; Debes et al, 2018). Bose et al (2011) analyzed a population of pregnant women, which is very different from our population of HIV-infected patients, and Debes et al (2018) analyzed only the seroprevalence of HEV infection associated with the presence of the PROGINS gene and they did not differentiate between sexes, a variable in which we found differences. In addition, both of these studies focused their analyses on those with PROGINS versus those who were not carriers of this allele, without specifying homozygosity.…”
Section: Discussionmentioning
confidence: 88%
“…PROGINS has also been reported to influence the activity of the immune system (Lhomme et al, 2016) and have an impact on the clinical features and evolution of viral infections. In this context, the PR has been studied in relation to hepatitis E virus (HEV) infection (Bose et al, 2011; Debes et al, 2018), where those with the PROGINS gene were observed to develop a worse clinical course of hepatitis E. The aim of our study was to evaluate the influence of PROGINS on the susceptibility to and the clinical course of HEV infection in HIV patients in an area with high prevalence and incidence of hepatitis E.…”
Section: Introductionmentioning
confidence: 99%
“…A group of 187 healthy samples previously described were used as controls. 9 We obtained approval for our study by the Medical Ethical Review Board of the Erasmus Medical Center (reference number MEC-2011-438). LGC genomics, Huddleston, UK) were employed.…”
Section: Samplesmentioning
confidence: 99%